decompose expression into a sum of partial fraction

-22/`(x^(2)+3x-28)`

### 1 Answer | Add Yours

`x^2+3x-28`

`= x^2+7x-4x-28`

`= x(x+7)-4(x+7)`

`= (x+7)(x-4)`

`(-22)/(x^2+3x-28) = (-22)/((x+7)(x-4))`

`(-22)/(x^2+3x-28) = A/(x+7)+B/(x-4)`

`-22 = A(x-4)+B(x+7)`

When x = 4

`-22 = Bxx11`

`B = -2`

When x = -7

`-22 = Axx(-11)`

`A = 2`

*So the answer is;*

`(-22)/(x^2+3x-28) = 2/(x+7)-2/(x-4)`

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes